2014
DOI: 10.1590/0074-0276140125
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between Aedes aegypti identification in the field and in the laboratory after collection with a sticky trap

Abstract: Currently, sticky traps are regularly employed to assist in the surveillance of Aedes aegypti infestation. We tested two alternative procedures for specimen identification performed by local health agents: directly in the field, as recommended by certain manufacturers, or after transportation to the laboratory. A total of 384 sticky traps (MosquiTRAP) were monitored monthly during one year in four geographically representative Brazilian municipalities. When the same samples were inspected in the field and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Previous works 5 – 11 reported limited information, such as the focal length, background, and illumination (wavelength and intensity), when acquiring data. To address the problem, we built a piece of hardware called the Aedes Detector to improve the image acquisition, training and testing processes of the model.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works 5 – 11 reported limited information, such as the focal length, background, and illumination (wavelength and intensity), when acquiring data. To address the problem, we built a piece of hardware called the Aedes Detector to improve the image acquisition, training and testing processes of the model.…”
Section: Methodsmentioning
confidence: 99%
“…Despite numerous studies demonstrating the ability of a DCNN to provide 80 to 97% accuracy to classify medically important mosquitoes 7 – 11 , 15 , 16 , these results that use a large pretrained model might not be practical when deployed in hardware/devices. We deployed the proposed model in a platform called p5.js visual coding tool written in JavaScript by using the microcomputer of the Aedes Detector to verify the proficiency of the model at classifying a mixture of three different generations of mosquitoes in real time.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…aegypti captured using the sticky trap MosquiTRAP [24]. However, a later study found that mosquito identification in the laboratory was superior to that performed in locus by trained field agents [25]; divergent results presented by these studies may be due to differences in the way the field agents were trained and qualified.…”
Section: Gravid Mosquito Trapsmentioning
confidence: 99%
“…albopictus in the state of Acre, since 2020 14 , but without an official record of any findings of the immature forms or adults of this species. The methods used for the surveillance of Aedes with medical importance, especially Aedes aegypti , are highly dependent on human operation and skills to identify the mosquito species, both in the field and laboratory; therefore, it is important to invest time and resources in the training and qualification of health agents 15 .…”
Section: Figurementioning
confidence: 99%